Experimental vapor-liquid phase equilibrium analysis of the binary systems of aniline with xylene isomers at 93.13 kPa - Yadav, Satyajeet S.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2020)
In the present work, vapor-liquid phase equilibrium (VLE) analyses of binary systems of aniline with four isomers of xylene, comprising p-xylene, m-xylene, o-xylene, and ethylbenzene, are reported at 93.13 kPa. The experimental VLE data was generated in a dynamic circulating vapor-liquid, and the data was found thermodynamically consistent using the Van Ness point-to-point consistency test. The experimental VLE data was regressed with the Wilson, NRTL, and UNIQUAC activity coefficient models to obtain the binary interaction parameters. No azeotropic or close-boiling behavior was observed in any of the binary pair, and these pairs were found suitable for separation through a conventional distillation method.